Analysis of the financial literacy index of MSMEs 4.0 and its determinants - Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Lili Astika (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The financial literacy index of the Indonesian population has increased, yet cases of illegal online loan scams and fraudulent online transactions remain high due to low financial literacy. This study analyzes the financial literacy index of MSME 4.0 entrepreneurs in Tebing Tinggi City and its determinants to support the formulation of appropriate policies. The examined variables include education level, age, business turnover, and gender. Primary data were collected through questionnaires from 100 MSME entrepreneurs using e-commerce and social commerce platforms. Data analysis was conducted using multiple linear regression. The results indicate that the financial literacy index of MSME 4.0 entrepreneurs in Tebing Tinggi City is relatively high (82.26 percent). Education has a positive and significant effect on financial literacy, while age and business turnover have a negative and significant effect. Gender has a positive but insignificant effect. The implications of this study emphasize the importance of improving access to financial education, particularly for older entrepreneurs and those with higher business turnover, to enhance their understanding of modern financial technology.